Can the Poor Influence Policy? : Participatory Poverty Assessments in the Developing World - Kende-Robb, Caroline (International Monetary Fund, 2002)
The second edition of this book outline show to include the poor using the Participatory Poverty Assessment (PPA) method. This method was developed by the World Bank in partnerships with NGOs, governments, and academic institutions, and has been implemented in over 60 countries worldwide duringthe last decade. This book also draws on new PPA case examples. Joint publication with the World Bank.